Developing the Russian Index of Elderly Population Well-Being: Principles and Conceptual Framework; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Pavlova I. A. Irina Anatolievna (2017, 2017)
Title screen